KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKA - Prastyowati, Moga; Oktarina, Nina; Rokhman, Fathur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Leadership is the core of an organization and plays a very important role, because the leader is the main person who determines the black and white of the organization under him. A leader is required to be adaptive to developments and changes in the times. The dynamic education system in Indonesia also requires the headmaster as a leader in the education unit to be ready to follow changes in existing policies. The current policy is about implementing an independent curriculum in the context of learning recovery. The readiness of all stakeholders to face curriculum changes is a challenge for headmasters so that this policy does not become a new problem for the education unit. Responsive headmaster leadership that can improve teacher readiness and performance is one solution to this challenge, namely transformational leadership. Transformational leadership is the process of leaders influencing followers by providing high motivation regarding the importance of performance values through empowerment so that changes occur for the better in realizing organizational goals. The principal's role is to influence all elements in the school to create strategies and innovations by utilizing the school's resources by providing strong motivation so as to increase one's moral values and develop one's competence so that one is ready to move together to implement the independent curriculum.